Pspice realization of the Uçar prototype delay model - Uçar, Ahmet; Mishra, Deepak (Freund Publishing House Ltd, 2006)
Pspice model of an autonomous continuous-time difference-differential equation with one variable, known Uçar prototype model is developed and its complex dynamics is investigated. Pspice realization of each block of the model is discussed explicitly. Limit cycle and chaotic behaviors of the model are observed experimentally. The effects of different values of time delay on the model behavior are observed. Comparing the results of Pspice model and Matlab/SIMULINK simulation, the results are satisfactory. © Freund Publishing House Ltd.
Keywords: Chaos; Difference-differential equations; Pspice modeling; Uçar model